E-Governance of skill training programme under Garib Kalyan Rojgar Abhiyaan - ARORA, ALKA; PAL, SOUMEN; NAHA, SANCHITA; MARWAHA, SUDEEP; BURMAN, R R; KUMAR, SOURABH; ADHIGURU, P; POSWAL, R S; SINGH, A K (The Indian Journal of Agricultural Sciences, 2022)
Garib Kalyan Rojgar Abhiyaan (GKRA) initiative was announced by the government of India in June 2020 for a period of 125 days to create livelihood opportunities for the returned migrants in their states and to sustain rural development. GKRA was convergent effort between 12 different ministries/departments covering 25 activities over 116 districts of 6 states. As different stakeholders were involved, therefore for effective monitoring and data exchange an IT platform was created at central level (https://gkra.nic.in) where all departments exchanged data for consecutive 15 weeks. Indian Council of Agricultural Research (ICAR) organized skill development training programmes for livelihood through Krishi Vigyan Kendra (KVK). E-Governance of these training programmes and exchange of data to central GKRA portal was managed through a module developed during July-October 2020 under KVK Knowledge Network Portal (https://kvk.icar.gov.in) at ICAR-Indian Agricultural Statistics Research Institute and hosted at ICAR Data Centre, ICAR-IASRI, New Delhi. The emphasis of the training programmes was on the areas of integrated farming to support livelihood. Overall, the participants were satisfied with the quality of training programmes conducted by KVKs. KVKs also supported participants in handholding of technology and setting up their own venture. IT platforms provided efficient storing and retrieval of data, framework for exchange of information and enhanced visibility in the initiative.